Factors Influencing the Microwave‐Induced Expansion of Starch‐Based Extruded Pellets under Vacuum. Issue 3 (5th March 2014) - Kraus, Stefan; Schuchmann, Heike P.; Gaukel, Volker
Abstract The microwave‐induced expansion of starch‐based extruded pellets under vacuum was investigated in order to understand the underlying mechanisms. Microwave power (400, 600 and 800 W), system pressure (20, 50, 100 and 190 mbar) and initial sample mass (100, 200 and 300 g) were selected as influencing factors. During processing, the surface temperature of the matrix mainly depended on the moisture content, independent of the process parameters applied. A kinetic factor τ was calculated, which accounts for the time necessary to remove 1 g of water from the product. This factor is a reasonable measure for the kinetics of mass transfer. The higher the power absorption of the product, the smaller the values for τ and the faster the kinetics for heat and mass transfer. This can cause a higher supersaturation of the matrix before nucleation occurs. In turn, a higher number of bubbles can be nucleated, and the resulting pore areas are shifted to smaller values. While decreasing τ from 22.6 to 5.9 s/g H2O, volume expansion increases from 0.82 to 1.49 with an increased number of pores (1.7/mm2 to 3.4/mm2) created, even when the pore areas are comparably smaller. System pressure does not significantly alter the expansion because in the investigated range, neither nucleation nor bubble growth is changed. However, it is important to keep the system pressure below a certain value (190 mbar); otherwise, coagulation of the moist pellets occurs, thus rendering the process unstable. Practical Applications In contrast to directly expanded extruded snacks, third‐generation snacks are produced by predrying nonexpanded, extruded pellets, followed by expansion to achieve a crispy and porous texture. Using this process route, extrusion can be performed at high moisture content, moderate temperature and shearing condition. This is beneficial in terms of preserving thermally and mechanically sensitive ingredients. A special feature of the process investigated in this study is that the expansion is achieved using microwave vacuum process, which allows an indirect expansion without the time‐ and energy‐consuming predrying process. This study shows that the total volume and inner structure of the pellets is influenced by process parameters in the expansion step, thus allowing producers to turn structure‐related properties, such as crispiness and crunchiness, into target values.